COGNITIVE INDEPENDENCE OF STUDENTS: ESSENCE, MAIN CHARACTERISTICS, STRUCTURE - Mikhno, S.V. (Pedagogy of Higher and Secondary Education, 2008)
The article is devoted to further defining of cognitive student’s independence more exactly, to the determination ofitsdwracteristics and structure